2007
DOI: 10.1002/mds.21479
|View full text |Cite
|
Sign up to set email alerts
|

[123I] FP‐CIT spect study in vascular parkinsonism and Parkinson's disease

Abstract: There is substantial evidence to support a role for small vessel disease (SVD) as a cause for vascular parkinsonism (VP). Using [(123)I] FP-CIT SPECT (single photon emission computed tomography), we have tried to determine whether VP patients have pre-synaptic dopaminergic function similar to PD patients, and whether the severity of parkinsonian symptoms as well as the levodopa response in VP patients are correlated with pre-synaptic dopaminergic dysfunction. Thirteen patients fulfilling operational clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 37 publications
8
73
0
7
Order By: Relevance
“…Statistically significant difference was noted in the neuroimaging findings like multiple territory involvement (p<0.001), periventricular white matter changes, subcortical white matter changes (p<0.001), basal ganglia ischemia (p<0.001). This is comparable to the findings reported in other studies 7,9 The most important neuroimaging findings reported in these studies were multiple vascular territory involvement, periventricular white matter changes, subcortical ischemic white matter changes, and ischemia of the basal ganglia and brainstem.…”
Section: Comparison Of Sample Patients With Vascular Parkinsonism Andsupporting
confidence: 91%
“…Statistically significant difference was noted in the neuroimaging findings like multiple territory involvement (p<0.001), periventricular white matter changes, subcortical white matter changes (p<0.001), basal ganglia ischemia (p<0.001). This is comparable to the findings reported in other studies 7,9 The most important neuroimaging findings reported in these studies were multiple vascular territory involvement, periventricular white matter changes, subcortical ischemic white matter changes, and ischemia of the basal ganglia and brainstem.…”
Section: Comparison Of Sample Patients With Vascular Parkinsonism Andsupporting
confidence: 91%
“…Most specialists would argue that differentiation would be possible by means of assessing levodopa responsiveness and olfaction. To further complicate matters, Zijlmans et al 38 have reported good or excellent responses to levodopa in 12 of 17 patients with pathologically confirmed VP. The use of the University of Pennsylvania Smell Test may be a helpful discriminator since olfaction is appa rently preserved in patients with VP, whereas 80% of patients with PD are hyposmic 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Reports on DAT binding in vascular PS provide heterogeneous results, which might indicate that vascular PS is a mixed entity that is not yet well characterized (40). Some authors have reported normal or only a slight but insignificant reduction of DAT binding in patients with suspected vascular PS (45,54,55); others have found significantly reduced binding values (56,57). This discrepancy may be attributed to differences in patient populations and the relatively small numbers of subjects investigated.…”
Section: Vascular Psmentioning
confidence: 99%